Development Of Electrochemical Biosensor Systems For Chlorpyrifos Pesticide Detection - Omer, Abdu Idris (2002)
Environmental monitoring systems are of great interest and highly significant in our life since every day we are exposed to many and various dangerous and fatal contaminants. Organophosphate pesticides such as Chlorpyrifos are widely used in agriculture to eliminate plant destroying pests. However, these pesticides may affect the environmental equilibrium unless continuous monitoring on their presence in water, soil, and agricultural products is carried out to protect human health and other living organisms. One of the approaches that can be adopted is to develop an on-line monitoring system. The widely used electronic and computer technology can simplify the development process of acquiring and monitoring system. In addition, the invention of biosensors to detect biologically-based materials such as Chlorpyrifos pesticide in the agricultural sector, glucose level in blood, heavy elements in the drinking water etc., have attracted interest.